Highly specific fiber optic immunosensor coupled with immunomagnetic separation for detection of low levels of Listeria monocytogenes and L. ivanovii - Mendonça, Marcelo (BioMed Central, 2012)
BACKGROUND: Immunomagnetic separation (IMS) and immunoassays are widely used for pathogen detection. However, novel technology platforms with highly selective antibodies are essential to improve detection sensitivity, specificity and performance. In this study, monoclonal antibodies (MAbs) against Internalin A (InlA) and p30 were generated and used on paramagnetic beads of varying diameters for concentration, as well as on fiber-optic sensor for detection. RESULTS: Anti-InlA MAb-2D12 (IgG2a subclass) was specific for Listeria monocytogenes and L. ivanovii, and p30-specific MAb-3F8 (IgM) was specific for the genus Listeria. At all bacterial concentrations (10(3)–10(8) CFU/mL) tested in the IMS assay; the 1-μm diameter MyOne beads had significantly higher capture efficiency (P < 0.05) than the 2.8-μm diameter M-280 beads with both antibodies. The highest capture efficiency for MyOne-2D12 (49.2% for 10(5) CFU/mL) was significantly higher (P < 0.05) than that of MyOne-3F8 (16.6 %) and Dynabeads anti-Listeria antibody (9 %). Furthermore, capture efficiency for MyOne-2D12 was highly specific for L. monocytogenes and L. ivanovii. Subsequently, we captured L. monocytogenes by MyOne-2D12 and MyOne-3F8 from hotdogs inoculated with mono- or co-cultures of L. monocytogenes and L. innocua (10–40 CFU/g), enriched for 18 h and detected by fiber-optic sensor and confirmed by plating, light-scattering, and qPCR assays. The detection limit for L. monocytogenes and L. ivanovii by the fiber-optic immunosensor was 3 × 10(2) CFU/mL using MAb-2D12 as capture and reporter antibody. Selective media plating, light-scattering, and qPCR assays confirmed the IMS and fiber-optic results. CONCLUSIONS: IMS coupled with a fiber-optic sensor using anti-InlA MAb is highly specific for L. monocytogenes and L. ivanovii and enabled detection of these pathogens at low levels from buffer or food.